Refusal of The Amil Concept in Improving Understanding of Arabic Language Rules (Examining The Thoughts of Ibn Madla') - Hikamudin Suyuti, Muh. (Proceeding of Dakwah Saizu International Conference, 2023)
Understanding the rules of the Arabic language is the basis for rejecting the science of nahwu, especially related to amil, because amil is the estuary of the complexity of understanding the rules of the Arabic language. This research is a qualitative research using the library research method by collecting scientific data in the form of historical books and the development of nahwu from time to time and then processing the data so that it is systematic, rational and valid. The purpose of this research is to find out the language in the development of Arabic rules, especially nahwu, experience a tug-of-war against the rejection of these rules because they find it difficult for knowledge seekers to understand the rules of Arabic, especially nahwu. The result of this study is Ibn Madla''s rejection of the concept of ámil which was held by the majority of scholars for several centuries since Nahwu was written by Sibawaih, basically based on the spirit of facilitating Arabic grammar, aimed at religious interests, so that any elements raised by scholars for interpreting language data, and the elements of nahwu are not part of the language, and are also unnecessary and must be discarded.